Financial System Impact of Disruptive Innovation - United Nations Environment Programme (UNEP, 2016)
This report examines disruptive innovations and their implications for the design of a green and inclusive financial system – innovations driven by top-down, centralised innovation in policy and regulation or by bottom-up, decentralised financial market innovation innovations stimulated by long-terms shifts in environmental and social factors or technological innovations. The scale of the challenge of the transition to such a system calls for flexibility and experimentation with a diverse set of policy approaches."